Language Games and Meaning as Used in Student Encounters With Scientific Literacy Test Items. Issue 2 (2nd December 2015) - SERDER, MARGARETA; JAKOBSSON, ANDERS
ABSTRACT: Previous research in science education has suggested that difficulties among students learning science relate to challenges in framing its discourse. This article examines the role that language plays in a scientific literacy test for which everyday life is an augmented aspect. Video‐recorded data was collected in four ninth‐grade science classes in a Swedish compulsory school as small groups of students discussed and collaboratively solved Programme for International Student Assessment (PISA) science test items. The theoretical framework assumes sociocultural perspectives as well as that of Wittgenstein's later works on language. The study involves an analysis of students' meaning making of specific words that occur in the test and the various language games to which these words contribute. Specifically, we analyzed the students' use of four different words: reference, constant, pattern, and factor. We found that the students use these words in everyday or mathematical language games; for example, understanding the word "pattern" as a mathematical regularity rather than a result of a scientific experiment. The results were analyzed in relation to the specific illustrations and wording that contextualize the items. We argue that a crucial part of being scientifically literate is privileging science content over other possible disciplines and contexts and ignoring the everyday perspective.